Pengaruh Disiplin Kerja, Motivasi Kerja dan Kompensasi Terhadap Kinerja Karyawan Respati Sanur Beach Hotel - Krisnanda, Nyoman Angga; Sudibya, Gede Adnyana (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
The purpose of this research is to know influence of work discipline, work motivation and compensation to good employee performance simultaneously and partial also to know dominant variable than influence the employee performance. Respati Sanur Beach Hotel is the researcher location with 51 employees as respondent. Data analysis techniques used to test the hypothesis is couple linear regression analysis that has a purpose to know the simultaneous and partial influences also to determine dominant variable that influences employee performance. Based on the analysis result we know that work discipline variable, work motivation and compensation significant simultaneously to Respati Sanur Beach employee performance with contribution number is 64,3 percent. Work discipline variable, work motivation and compensation has positive influences and significant partially to employee performance at Respati Sanur Beach Hotel with variable compensation as the most influence variable to employee performance.
Keywords: employee performance, work discipline, work motivation and compensation